Éléments d’explication sociale de l’uxoricide - Boisvert, Raymonde (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1996)
In this article, we will focus on the frequency and characteristics of conjugal homicides which occurred in Montréal between 1954 and 1962, and compare these crimes with those taking place between 1985 and 1989. The comparison of the main aspects of the phenomenon shows that the number of such crimes has increased steadily from one period to the next. During these two periods, women formed the majority of the victims and men, the perpetrators. The individual factors (mental illness, alcohol, despair) that may trigger the expression of violence do not account for all homicides. In fact, these crimes are often the ultimate demonstration of the control some men have over their wives. We will examine the social implications lying at the root of some men's desire to control their wives to the point of killing them when they fail to meet their expectations.